YOSEMITE and RHINE: Phase 3 Randomized Clinical Trials of Faricimab for Diabetic Macular Edema: Study Design and Rationale - Eter, Nicole, MD, PhD; Singh, Rishi P., MD; Abreu, Francis, PhD; Asik, Kemal, PhD; Basu, Karen, PhD; Baumal, Caroline, MD; Chang, Andrew, PhD; Csaky, Karl G., MD; Haskova, Zdenka; Lin, Hugh, MD; Ruiz, Carlos Quezada, MD; Ruamviboonsuk, Paisan, MD; et al. (Ophthalmology science (Online), 2022)
AbstractObjectiveFaricimab is a novel anti–angiopoietin-2 (Ang-2)/anti–vascular endothelial growth factor (VEGF) bispecific antibody with high affinities and specificities for both VEGF and Ang-2. It is postulated that targeting angiogenic factors and inflammatory pathways in addition to the VEGF pathway will increase treatment durability and improve outcomes. The phase 3 YOSEMITE (NCT03622580) and RHINE (NCT03622593) trials are designed to assess the efficacy, safety, and durability of faricimab compared with aflibercept in patients with diabetic macular edema (DME). The trials will evaluate a personalized treatment interval (PTI) approach to address heterogeneity in treatment response among patients with DME. DesignTwo identically designed, global, double-masked, randomized, controlled phase 3 trials (YOSEMITE and RHINE). ParticipantsAdults with center-involving DME secondary to type 1/2 diabetes mellitus. MethodsThese studies were designed to evaluate 3 treatment groups: faricimab 6.0 mg dosed either at fixed dosing every 8 weeks (Q8W) after initial treatment with 6 intravitreal doses at 4-week intervals (Q4W), or faricimab 6.0 mg dosed according to PTI after initial treatment with 4 Q4W doses, compared with aflibercept 2.0 mg dosed Q8W after 5 initial Q4W doses. The primary end point of the studies was change from baseline in best-corrected visual acuity at 1 year, averaged over weeks 48, 52, and 56. Secondary end points included anatomic, durability, and patient-reported outcomes. Safety outcomes included incidence and severity of ocular and nonocular adverse events. The PTI is a protocol-defined flexible regimen based on the treat-and-extend concept, which allowed up to every-16-week (Q16W) adjustable dosing based on objective and standardized criteria. The PTI design aimed to maximize therapeutic results while minimizing treatment burden. Main Outcome MeasureWe describe the rationale for the study design and the novel PTI (up to Q16W adjustable dosing) approach for treatment with faricimab. ResultsYOSEMITE and RHINE enrolled 940 and 951 patients, respectively. Results from each study will be reported separately. ConclusionsYOSEMITE and RHINE were the first registrational trials in retinal disease to incorporate an objective PTI regimen, allowing for up to Q16W adjustable dosing with a dual Ang-2/VEGF-A inhibitor, faricimab 6.0 mg, for the treatment of DME.